Reducing family and school-based violence at scale: a large-scale pre–post study of a parenting programme delivered to families with adolescent girls in Tanzania - Joyce Wamoyi; Jamie Lachman; Yulia Shenderovich; Qing Han; Mackenzie Martin; Francisco Antonio Calderón Alfaro; Samwel Mgunga; Esther Nydetabura; Nyasha Manjengenja; Mwita Wambura (BMJ Global Health)
Background Parenting programmes, including those delivered in the Global South, are effective strategies to reduce violence against children (VAC). However, there is limited evidence of their impact when implemented at scale within routine delivery systems. This study aimed to address this gap by evaluating the real-world delivery of Parenting for Lifelong Health for Teens in Tanzania.Methods Participating parents/caregivers and their adolescent girls were recruited by local implementing partners in 2020–2021 as part of a community-based HIV prevention initiative focused on addressing drivers of female adolescent HIV-vulnerability such as VAC, caregiver–adolescent relationships and sexual reproductive health communication. The 14-session, group-based parenting programme was delivered by trained teachers and community facilitators. Quantitative surveys administered by providers measured a variety of outcomes including child maltreatment (primary outcome) and multiple secondary outcomes linked to increased risk of VAC. Multilevel models examined pre–post effects as well as variation by attendance and baseline demographic variables.Results Pre–post data from 27 319 parent/caregiver–child dyads were analysed, of which 34.4% of parents/caregivers were male. Analyses showed large reductions in child maltreatment (parents/caregivers: IRR=0.55, (95% CI 0.54, 0.56); adolescents: IRR=0.57, (95% CI 0.56, 0.58)), reduced intimate partner violence experience, reduced school-based violence, increased communication about sexual health, reduced poor supervision, reduced financial insecurity, reduced parenting stress, reduced parent and adolescent depression, and reduced adolescent conduct problems. In contrast to these positive outcomes, parents/caregivers and adolescents also reported reduced parental positive involvement and support of education, with those experiencing greater adversity reporting less change than those with less adversity.Conclusions This study is the first to examine the large-scale implementation of an evidence-based parenting programme in the Global South. Although additional research is necessary to examine potential negative effects on positive parenting and parent support of education, findings suggest that Furaha Teens can sustain its impact on key outcomes associated with VAC when delivered at scale.